Educational creative task as the main teaching tool for formation of compositional abilities of prospective leaders of the studio of decorative and applied creativity - Ekaterina S. Sachkova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The traditional nature of the professional training of prospective leaders of the Studio of decorative and applied creativity in high school does not take into account the specifics of the professional tasks of the leader of the Studio of decorative and applied creativity and the importance of compositional abilities for their effective solution. The aim of the study presented in this article is to determine the complex of pedagogical tools necessary and sufficient to ensure the successful development of the process of formation the compositional abilities of prospective leaders of the Studio of decorative and applied creativity in the course of professional training at the University.The methodological basis of the study is a functional approach, involving the consideration of pedagogical processes, objects, phenomena as systems and identifying the components of these systems structural elements, their functions in relation to the system as a whole, relationships and roles performed in relation to each other. In the process of research the theoretical analysis of pedagogical, psychological, methodological literature on the problem of research and empirical methods: pedagogical observation, testing, stating and forming experiments.As a result of the research the specificity of compositional activity in the sphere of decorative and applied art is revealed, the definition and structure of compositional abilities of leaders of the Studio of decorative and applied creativity is formulated, the complex of pedagogical means of formation of compositional abilities of students of higher education institutions of culture and arts - prospective leaders of the Studio of decorative and applied creativity is developed and tested.The formation of compositional abilities of prospective leaders of the Studio of decorative and applied creativity is carried out in the process of specially organized activities, the main content of which is the solution in the prescribed manner and combinations of educational and creative composite tasks presented in various techniques of decorative and applied art and in computer performance, having a certain level of complexity, subjects and orientation. The method of diagnostics of level of formation of compositional abilities of students is the qualitative assessment by the expert on criteria of visual perception of results of accomplishment by students of control compositional tasks. Efficiency of application of means of formation of compositional abilities of the prospective leaders of the Studio of decorative and applied creativity is reflected the qualitative growth of indicators in the structure of compositional abilities.